Exploring drivers of customer loyalty in themed Korean cuisine: insights from the developing Korean restaurant industry in Makassar, Indonesia - Fadzila, Nurhayatul; Munir, Abdul Razak; Bukenya, James O.; Akzar, Rida; Kamarulzaman, Nitty Hirawaty; Nishantha, Busige; Darma, Rahim (Frontiers Media SA, 2026)
Sensory experiences and digital communication increasingly shape how visitors perceive, evaluate, and revisit tourism and hospitality venues. In themed restaurants, visitor experiences are co-constructed through social media communication and multisensory in-store environments. This study examines the influence of social media marketing (SMM) and sensory marketing (SM) on revisit intention, with customer satisfaction as a mediating mechanism, using data from Korean restaurants in the United States. Drawing on the Uses and Gratifications Theory, Experience Economy Theory, and the Stimulus–organism–response (S-O-R) framework, this study proposes an integrated model that explains how communicative and sensory stimuli jointly shape cognitive–affective responses and behavioral outcomes. Data from 175 restaurant visitors were analyzed using partial least squares structural equation modeling (SEM-PLS). The findings show that both SMM and SM significantly influence revisit intention directly and indirectly through customer satisfaction, with sensory marketing having the strongest total effect. The results highlight the importance of aligning digital communication with embodied sensory experiences to enhance visitor satisfaction and loyalty, offering a transferable framework for understanding experience-mediated communication in the tourism and hospitality settings.